Project financial evaluation on the context of Bosch Suppliers Club initiative - Francisco, Pedro Martins (2020)
The present work aims to answer a problem identified by Bosch Car Multimedia. The partner companies in the “Clube de Fornecedores” initiative, despite showing good technical and scientific skills, reveal little knowledge about financial analysis of investment projects. Thus, a financial analysis of a project was carried out between Bosch and a hypothetical supplier company, with the objective of creating a framework that any company can apply, to evaluate its own projects. For this, an analysis of the literature on project evaluation methods was carried out, and the conclusion reached was that the most appropriate method, considering the type of project being evaluated, would be the Expected Net Present Value (ENPV). We proceeded with an analysis of the methodology to estimate the necessary inputs of the ENPV. Then, the financial evaluation of the project was made, which returned an ENPV of 349 177,10€, which means that the project should be accepted. Finally and complementary, a risk analysis was carried out, with the results suggesting the financial viability of the project.